Petrogenesis of the paleoproterozoic ultramafites in Wuchuan area, Inner Mongolia: implications for tectonic evolution - Hu, Hao; Zhong, Dongyan; Zhou, Zhiguang; Wang, Guosheng; Gao, Shen; Chen, Jianfeng; Feng, Chenfei (Frontiers in Earth Science, 2024)
IntroductionThe east-west trending Khondalite Belt, located on the northern margin of the North China Craton, is linked to the Paleoproterozoic Columbia supercontinent’s evolution. However, the relationship between the Khondalite Belt formation and orogenic processes remains unclear.MethodsField investigations, petrology, zircon U-Pb dating, whole-rock geochemistry, and electron probe mineral thermobarometry.ResultsGarnet-bearing pyroxenite and serpentinite-like dunite in the ultramafites have zircon U-Pb ages of (1947 ± 17) Ma and (1960 ± 25) Ma, respectively. The rocks show characteristics of subalkaline tholeiitic basalt series, with low SiO2 (35.79%–50.77%), TiO2 (0.01%–0.71%), Al2O3 (0.17%–3.39%), and alkalis (0.02%–2.01%), but high Fe2O3 (12.92%–15.06%). These rocks are enriched in light rare earth elements with slight depletion of Eu, enriched in large ion lithophile elements (Rb and K), and depleted in high field strength elements (P, Zr, and Hf).DiscussionThese metamorphic environments imply that the conditions for ultramafites formation were insufficient to induce granulite-facies metamorphism in the surrounding rocks, indicating that granulite-facies metamorphism in the Khondalite Belt is not closely related to post-orogenic extension in the Inner Mongolia-Northern Hebei orogenic belt.